2002
DOI: 10.1046/j.1095-8312.2002.00082.x
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA distributions indicate colony propagation by single matri-lineages in the social spider Stegodyphus dumicola (Eresidae)

Abstract: Colony‐dwelling social spiders of the genus Stegodyphus are characterized by high colony turnover, within‐colony mating, inbreeding and skewed sex ratios. These phenomena may purge genetic variation from the entire species gene pool. Social Stegodyphus have previously been discussed as ecologically unstable and evolutionary dead ends. We investigated the distribution and age (sequence divergence) of mitochondrial DNA variation for inferences of colony propagation, colony discreteness and maintenance of genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
90
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(99 citation statements)
references
References 34 publications
8
90
1
Order By: Relevance
“…containing multiple retreats), where smaller colonies will 'bud' off from the natal colony and share a single large capture web [36]. Although it is unknown if these budding individuals are also more likely to engage in long-distance dispersal to find new clusters of colonies [39], evidence from mitochondrial DNA suggests that colonies in close proximity are formed from single matri-lineage propagules, and thus local population dynamics are strongly influenced by individual behavioural decisions [40]. The propensity for individuals to leave the colony, in turn, seems to be influenced by group size (as in other social groups [41]), but an individual's decision to bud off from the natal colony may be influenced by individual-level traits (i.e.…”
Section: (A) Web Architecture and Dispersalmentioning
confidence: 99%
“…containing multiple retreats), where smaller colonies will 'bud' off from the natal colony and share a single large capture web [36]. Although it is unknown if these budding individuals are also more likely to engage in long-distance dispersal to find new clusters of colonies [39], evidence from mitochondrial DNA suggests that colonies in close proximity are formed from single matri-lineage propagules, and thus local population dynamics are strongly influenced by individual behavioural decisions [40]. The propensity for individuals to leave the colony, in turn, seems to be influenced by group size (as in other social groups [41]), but an individual's decision to bud off from the natal colony may be influenced by individual-level traits (i.e.…”
Section: (A) Web Architecture and Dispersalmentioning
confidence: 99%
“…Moreover, Raven (1992) and Main (1992) suggested that L. hasselti may have only recently been introduced to eastern Australia from South Australia, which would explain the lack of genetic variation between the L. hasselti specimens. Although the ND1 mitochondrial gene region has previously been used to examine intra-specific variation between spider populations (Hedin 1997a;Hedin 1997b;Masta 2000;Johannesen et al 2002;Maddison & Hedin 2003;Masta & Maddison 2002), this gene region did not evolve fast enough to pro-vide the definition required to examine gene flow between populations of L. katipo, L. atritus or L. hasselti. Moreover, the low number of samples examined in this project also made it difficult to gain a definitive view of intraspecific gene flow.…”
Section: Discussionmentioning
confidence: 99%
“…The ND1 gene region was chosen because it is fast evolving and has been successfully used to examine genetic differences between spider species and populations (Hedin 1997a(Hedin , 1997bMasta 2000;Johannesen et al 2002;Maddison & Hedin 2003;Masta & Maddison 2002;Vink & Paterson 2003).…”
mentioning
confidence: 99%
“…Mating between close relatives of the same cohort results in a high degree of inbreeding (Wickler and Seibt 1993). For S. dumicola females from Namibia, Johannesen et al (2002) showed that mitochondrial DNA variation is predominately distributed between colony clusters and each colony cluster is monomorphic for most loci. Nuclear DNA analysis of S. dumicola females confirmed low genetic variation among colony members (Smith DR, unpublished data).…”
Section: Methodsmentioning
confidence: 99%